Failure analysis of a water wall tube. (November 2020) - Ren, Facai; Xu, Jinsha; Si, Jun
Abstract: The failure reasons of a boiler water wall tube used in coal-fired power plant were analyzed by the chemical composition, optical microscope and scanning electron microscope analysis. The results of metallographic analysis show that the microstructure is ferrite and pearlite, pearlite has no obvious spheroidization. The comprehensive analysis results show that the abnormal oxidation erosion leads to the leakage failure of the water wall tube at the fire-facing side.